UPAYA PENINGKATAN ENTREPREUNERSHIP MELALUI INISIASI DAN PELATIHAN PENGEMASAN WEDANG PUCUK DAUN JATI (TECTONA GRANDIS L.F) - Suwahono Suwahono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The entrepreneurial spirit and value can be influenced through the initiation process, and business training. pharmacological analysis of teak shoots(Tectona Grandis l.f) had antibacterial, antioxidant, antifungal, antiinflammatory,antipyretic, analgesic, anti-diuretic, and hypoglycemic activity.The use of teak leaves in the form of easy use should be disseminated andintroduced through initiation and entrepreneurship training. The results of thisstudied indicate had a significant influence betweeninitiation and training ofteak leaf packaging with the entrepreneurial spiritand  value. Keywords: Enterpreneurship, Tectona Grandis L.F